2017
DOI: 10.17116/oftalma201713334-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of corneal aberrations after intrastromal segments and MyoRing implantation using femtosecond laser in patients with keratoconus

Abstract: Implantation of intrastromal MyoRings leads to a greater reduction in the total corneal aberration, higher-order aberrations under photopic and mesopic conditions, and spherical aberration under photopic conditions as compared to ICS in patients with stage III KC; a comparable reduction in the total corneal, higher-order, and spherical aberrations under photopic conditions as compared to ICS in patients with stage II KC; a comparable increase in spherical aberration under mesopic conditions as compared to ICS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…A comparative study by Pashtaev et al 27 also demonstrated that ICCR treatment lead to a greater reduction in total corneal aberration, higher order aberrations (HOAs) and spherical aberration than the Keraring in KC eyes staged at Amsler–Krumeich III. Postoperative changes in Amsler–Krumeich II KC eyes were comparable in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparative study by Pashtaev et al 27 also demonstrated that ICCR treatment lead to a greater reduction in total corneal aberration, higher order aberrations (HOAs) and spherical aberration than the Keraring in KC eyes staged at Amsler–Krumeich III. Postoperative changes in Amsler–Krumeich II KC eyes were comparable in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Bamdad et al demonstrated superior reduction of asphericity and keratometry with MyoRing treatment as with the Keraring. 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, comparison to our study may not be appropriate. Pashtaev et al [17] compared different types of intrastromal implants and found better outcomes with the MyoRing. They partially attributed this outcome to the 360° insertion of the MyoRing [17].…”
Section: Discussionmentioning
confidence: 99%
“…Pashtaev et al [17] compared different types of intrastromal implants and found better outcomes with the MyoRing. They partially attributed this outcome to the 360° insertion of the MyoRing [17]. Studený et al [18] reported good outcomes at 12 and 24 months after MyoRing implantation.…”
Section: Discussionmentioning
confidence: 99%